Pendampingan Penyusunan Produk Hukum Daerah Tentang Retribusi Pelayanan Persampahan Pemerintah Kabupaten Lumajang - Wahyu Krisnanto; Victor Imanuel W. Nalle (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
The health condition of Indonesian citizens is guaranteed by the Constitution of the State of Indonesia. The constitutional guarantee mandates that the state is obliged to provide public health services to its citizens. One way to ensure that people have good health conditions is through the provision of waste management services. There was a paradigm shift after the issuance of Law No. 18 of 2008 on Waste Management, where waste management is not only the duty and responsibility of the Local Government but also the obligation of the community. Community involvement in waste management is included as a form of retribution in supporting waste management policies. Community involvement to contribute to waste management policies in the form of retribution for waste services needs to be supported by the existence of local legal products as the legal basis for collecting the retribution. In order to participate in development in the Lumajang Regency area, especially in the stage of preparing legal products in the form of Regional Regulations Concerning Public Service Retribution on Waste Services in 2021, community service is held in the form of mentoring activities. Assistance is provided to prepare Academic Papers and Draft Regional Regulations. Mentoring activities are carried out using the focus group discussion method and assistance in the preparation of legal products. With the implementation of this mentoring activity at the end of 2021, an Academic Paper and a Draft Regional Regulations Concerning Public Service Retribution on Waste Services have been compiled.